EVALUATION OF THE ECONOMIC EFFECT OF INVESTMENTS IN MARKETING INFORMATION SYSTEM - Serge E. Pyatovsky (Статистика и экономика)
The approaches to assessing the cost-effectiveness of marketing campaigns,the economic effect of the implementation in the organization of the marketing information system (MIS) are analyzed. The problems of assessment of investmentsin MIS are submitted.